An Analysis of Loan Loss Provisioning Behaviour in Hong Kong Commercial Banks - Xu, Binxing (2016)
This study investigates the determinants of loan loss provisioning behaviour in Hong Kong commercial banks based on the sample of 20 banks during the period of 2006-2014. We examine the income smoothing, capital management and business cycle hypotheses and test whether the inclusion of Cost efficiency has an impact on loan loss provisioning. The results show that the banks do not indicate the utilization on income smoothing and capital management of provisions, but both pro and counter cyclicality. We finally find a gradually changing trend from procyclical to countercyclical of loan loss provisioning in Hong Kong.